Children's vulnerability to natural disasters: Evidence from natural experiments in Bangladesh. (September 2020) - Ahsanuzzaman,; Islam, Muhammad Q.
Highlights: We use difference-in-difference method to construct counterfactual to estimate the impact of cyclones – Sidr and Aila – which have been considered as exogenous shocks to the affected households. Cyclone Sidr, a mega cyclone in Saffir-Simpson scale, lowered nutritional outcomes, height for age in particular, of the exposed children. Back to back two cyclones even with smaller scale made the children of affected households vulnerable. Exposure to climate shocks put children at risk of lowered lifetime development. Abstract: Both developed and developing countries face natural disasters, but it is the poor in developing countries, particularly women and children, that are most affected by those disasters in terms of loss of lives and livelihoods. If the predictions of climate change models bear out, Bangladesh could be affected by frequent and severe natural disasters such as rising sea levels leading to floods, cyclones, etc. Natural disasters adversely affect employment opportunities and earnings of the most vulnerable households. Loss of employment and earnings can affect the nutritional intake of children in regions affected by natural disasters. Since nutritional status in the early ages of 0–60 months of a child can potentially impact outcomes in adult life including education and earnings, hindrances that affect nutritional supply and result in low nutritional intake can have adverse lifetime effects on children. Consequently, the frequency and severity of natural disasters due to climate change have intergenerational effects. In this study, we examine the effects of natural disasters – specifically, cyclones Sidr and Aila - on children's nutritional status in Bangladesh. We estimate the nutritional status of children below 60-months age who had been exposed to those extreme events in November 2007 and May 2009. Results show that children exposed to such extreme climate events, while in-utero and newborn stages, suffer a significant reduction in height for age Z-score and are more likely to be stunted and underweight. This is particularly important as height for age Z-score is regarded as a critical measure of the long-term consequences of nutritional intake. Our findings suggest that extreme climate events such as super cyclones can potentially exert detrimental effects on nutritional status indicator that is an important measure of the long-term nutrition intake.